2009
DOI: 10.1098/rspb.2009.1014
|View full text |Cite
|
Sign up to set email alerts
|

A new mammal skull from the Lower Cretaceous of China with implications for the evolution of obtuse-angled molars and ‘amphilestid’ eutriconodonts

Abstract: We report the discovery of Juchilestes liaoningensis, a new genus and species of eutriconodont mammal from the Lujiatun Site of the Lower Cretaceous Yixian Formation (123.2 + 1.0 Ma; Lower Aptian). The holotype preserves a partial skull and full dentition. Among eutriconodonts, its lower dentition is similar to taxa formerly assigned to the paraphyletic group of 'amphilestids'. Some have considered 'amphilestid' molars to represent the structural intermediate between the lower molars of the 'triconodont' patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 38 publications
1
39
0
Order By: Relevance
“…Several Mesozoic clades that are parts of Mammalia (Fig. 5) have also been examined by CT-scanning including eutriconodonts (Gao et al, 2009;ZXL, unpublished data), multituberculates (Ladevèze et al, 2010), as well as the stem relatives of the living therian mammals, such as symmetrodonts and dryolestoids (Ruf et al, 2009;Luo et al, 2011a). Mesozoic eutherians and a wide range of early Cenozoic placental and marsupial mammals have also been studied in great detail (Horovitz et al, 2009;Ekdale, 2011;Ekdale & Rowe, 2011).…”
Section: Ear Structures In Mesozoic Mammaliaformsmentioning
confidence: 98%
“…Several Mesozoic clades that are parts of Mammalia (Fig. 5) have also been examined by CT-scanning including eutriconodonts (Gao et al, 2009;ZXL, unpublished data), multituberculates (Ladevèze et al, 2010), as well as the stem relatives of the living therian mammals, such as symmetrodonts and dryolestoids (Ruf et al, 2009;Luo et al, 2011a). Mesozoic eutherians and a wide range of early Cenozoic placental and marsupial mammals have also been studied in great detail (Horovitz et al, 2009;Ekdale, 2011;Ekdale & Rowe, 2011).…”
Section: Ear Structures In Mesozoic Mammaliaformsmentioning
confidence: 98%
“…3b on a data set of 111 taxa and 490 characters 7,28 ), and the other evaluates the placement of Spinolestes among 20 genera of eutriconodonts (Extended Data Fig. 3a, on the basis of 90 dental and mandibular characters 19,20,32,33 …”
Section: Phylogenetic Relationshipsmentioning
confidence: 99%
“…'Triconodonta' of Kermack et al (1973; see also Jenkins and Crompton 1979) has been repeatedly shown to be non-monophyletic by the consensus of researches over the last 20 years (e.g. Rougier et al 1996Rougier et al , 2007Luo et al 2002;Kielan-Jaworowska et al 2004;Gao et al 2010). We use the term Eutriconodonta as sensu lato throughout this paper unless otherwise noted, basically following Kielan-Jaworowska et al (2004); it includes 'amphilestid' eutriconodontans such as Hakusanodon and Juchilestes and differs from the Euriconodonta sensu Gaetano and Rougier (2011), which includes the tribe Volaticotheriini composed of Argentoconodon, Ichthyoconodon and Volaticotherium.…”
Section: Materials Methods and Terminologymentioning
confidence: 96%